PERBEDAAN HASIL BELAJAR KOGNITIF SISWA KELAS III PADA MATA PELAJARAN PKN MATERI HAK DAN KEWAJIBAN SEHARI-HARI MENGGUNAKAN MODEL PEMBELAJARAN WORD SQUARE DENGAN METODE CERAMAH DI GUGUS 3 KECAMATAN SITUBONDO KABUPATEN SITUBONDO TAHUN PELAJARAN 2016/2017 - Inne Indriyani Fauziyah; Reninda Dewi Pinar (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2016)
In order to create a learning process that encourages students can construct their own knowledge through active involvement in the learning process requires appropriate learning strategies. Good learning is learning always involves the students to solve a problem. Those problems can be solved by providing a learning model that suits the character of the student so that the learning objectives will be achieved. The problem of this research is Is there a significant difference to the cognitive learning third grade students on subjects that PKN using model Word Square with the lecture method? The method used in this research is quantitative research methods. The instrument used in this study are guidelines for observation, post test instruments, and documentation. Data analysis technique used is the t-test and procedure in this study through the preparation phase of research began to apply for the title until the submission of permit research to the test site and the implementation phase of research ranging from the preparation of research instruments, the implementation of classroom learning the control and the experimental class, pemeberian post test, data collection, data analysis, interpretation of data to draw conclusions. Having conducted a study and obtain the data, then the researchers analyzed the data by using t-test showed that there are differences in learning outcomes between students taught using learning model word square with the lecture method with a value of t = 4.27> t table = 2,000 at level 5% significance. Thus it can be concluded that there are differences in learning outcomes Differences Cognitive Learning Outcomes Student Class III In PKN Subject Matter Rights and Obligations in Everyday Life Learning Model Using Word Square Method Lecture At Force 3 District of Situbondo Situbondo in the school year 2016/2017 "